2019
DOI: 10.1111/ijcs.12554
|View full text |Cite
|
Sign up to set email alerts
|

Can traffic light nutritional labels induce healthier consumer choices? Experimental evidence from a developing country

Abstract: In a context of increasing health problems related to bad dietary habits in developing countries, simplified nutritional label formats may be a promising policy alternative. The aim of this study is to assess whether the multiple traffic light (MTL) system can improve the nutritional quality of consumer decisions. We conducted a selection experiment in Peru, where participants were offered a choice between three alternatives in two different food categories (crackers and beverages). Individuals were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
(43 reference statements)
0
10
0
2
Order By: Relevance
“…The selection process retrieved a total of 64 original publications, that reported 65 experimental studies, addressing the selected FOPNL and selected outcomes, as displayed on Table 2 [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection process retrieved a total of 64 original publications, that reported 65 experimental studies, addressing the selected FOPNL and selected outcomes, as displayed on Table 2 [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
“…When considering studies published from mid-2018, 47 new set of data were identified and analyzed [ 12 , 20 , 23 , 24 , 27 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 46 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 58 , 59 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 78 , 79 , 81 ]. Among those, 23 compared two of the four FOPNL of interest or more.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to caloric content, other researches (Boncinelli et al, 2017;Carels et al, 2006Carels et al, , 2007Defago et al, 2020) suggest that factors, such as the perceived fat content of food, come under the influence of the decision to place food in a healthy or dietary category.…”
Section: Measurement Validationmentioning
confidence: 99%
“…In addition to the functional objective itself, consumers maintain a wide variety of eating goals, such as symbolic or hedonic ones, as described by Bublitz et al (2013). Thus, the topic of healthy foods and their consumption has received significant attention from scholars (Defago et al , 2020; Goetzke et al , 2014; Hur and Jang, 2015; Joseph et al , 2011; Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%